2017
DOI: 10.1111/jfs.12333
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of acidic electrolyzed water treatments on the microbial reduction and control of enzymatic browning for fresh‐cut lotus root

Abstract: The disinfection efficacy of acidic electrolyzed water including slightly acidic electrolyzed water (SAEW) and strongly acidic electrolyzed water (AEW) on the fresh‐cut lotus roots and their effects on the appearance quality of fresh‐cut lotus root were evaluated in the present paper. The results showed that SAEW treatment could reduce the natural microbial flora populations as well as the inoculated populations of fresh‐cut lotus roots significantly. Also, our results obtained from the present study suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The highest decline in L* levels was observed for BA treated samples from both varieties throughout the storage period while the lowest was found for AEW treated samples, thus confirming the effectiveness of AEW as antibrowning agent reported in previous studies (Wang et al, 2007;Li et al, 2017). At the end of the storage period L* values were 70.7 and 72.0 for non-treated samples and 75.6 and 73.5 for AEW treated samples for 'Florina' and 'Ionathan' cultivars, respectively.…”
Section: Resultssupporting
confidence: 87%
“…The highest decline in L* levels was observed for BA treated samples from both varieties throughout the storage period while the lowest was found for AEW treated samples, thus confirming the effectiveness of AEW as antibrowning agent reported in previous studies (Wang et al, 2007;Li et al, 2017). At the end of the storage period L* values were 70.7 and 72.0 for non-treated samples and 75.6 and 73.5 for AEW treated samples for 'Florina' and 'Ionathan' cultivars, respectively.…”
Section: Resultssupporting
confidence: 87%
“…Li et al. () evaluated the disinfection efficacy of SAEW and strongly acidic electrolyzed water (AEW) on the fresh‐cut lotus roots and demonstrated that SAEW treatment could reduce the natural microbial flora populations significantly. Hao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Storage under refrigerated condition is one of the most commonly employed preservation methods to inhibit the deterioration of fresh meat due to microbial growth, and chemical and biochemical reactions, thus reducing microbial activity and increasing sensory shelf life (Allende, McEvoy, Tao, & Luo, 2009). However, certain complementary refrigeration sanitizing processes prior to the refrigeration storage should be developed and used to improve the safety and quality of fresh vegetables and meat (Li, Ren, Hao, & Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance was determined at 560 nm and one unit was defined as the number of enzymes that caused 50% inhibition of NBT per min. PPO activity was determined by the method of Li, Ren, Hao, and Liu (). The absorbance was determined by the oxidation of catechol at 420 nm and one unit was defined as 0.01 absorbance increased per min.…”
Section: Methodsmentioning
confidence: 99%